Young stellar objects in the region of dust bubble N1 - Alimgazinova, N.Sh. (Recent Contributions to Physics, 2025)
The study of young stellar objects is one of the key studies in astrophysics, as these objects provide a unique window into the processes that occur during the formation of stars and planets. Young stars are often found in clouds of gas and dust, which serve as a kind of "cradle" for their birth. Young stars, especially in massive star clusters, create powerful streams of wind and radiation that knock out dust and gas, creating ring structures, those as bubbles in molecular clouds. Analysis of such structures can provide additional clues about the strength of the interactions between stars and their environment at different stages of their evolution. The main objective of this study was to study the N1 dust bubble region and search for and identify young stellar objects. Searching for young stellar objects (YSOs) using infrared data from astronomical catalogs is an important and effective method for studying star formation. Young stars and their surroundings are often hidden from visible-light observations by dense clouds of gas and dust, but infrared radiation can penetrate these clouds, allowing astronomers to find objects that would otherwise be invisible. The identification of young stellar objects in this study was performed according to the algorithm of Koenig & Leisawitz (2014). The observational data of the WISE spacecraft in the near and mid-infrared bands W1 (3.4 μm), W2 (4.6 μm), W3 (12 μm) and W4 (22 μm) were used. Reliable non-zero fluxes of infrared radiation sources from the 2MASS and AllWISE catalogs were selected for the study. For the studied dust bubble, 7 objects of class I and 11 objects of class II were identified, 32 objects were assigned to the transition disk stage. For all identified young stellar objects, color diagrams were constructed showing the locations of the found objects with the corresponding evolutionary regions. Spectral indexes were calculated and energy distributions in the spectra were constructed for young stellar objects, which also confirmed their evolutionary status. The distribution maps of early-stage YSOs within the dust bubble are analyzed, which indicate the patterns of their distribution along filamentary structures in the dust bubble N1.